Beth & Amy - Kantra, Virginia (Berkley, 2021)
"Four sisters face new beginnings in this heartfelt modern take on Little Women by New York Times bestselling author Virginia Kantra. Amy March is more like her older sister Jo than she'd like to admit. An up-and-coming designer in New York's competitive fashion industry, ambitious Amy is determined to get out of her sisters' shadows and keep her distance from their North Carolina hometown. But when Jo's wedding forces Amy home, she must face what she really wants...and confront the One Big Mistake that could upend her life and forever change her relationship with Jo. Gentle, unassuming Beth grew up as the good girl of the family. A talented singer-songwriter, she's overcome her painful anxiety to tour with country superstar Colt Henderson. But life on the road has taken its toll on her health and their relationship. Maybe a break to attend her sister's wedding will get her out of her funk. But Beth realizes that what she's looking for and what she needs are two very different things.... With the March women reunited, this time with growing careers and families, they must once again learn to lean on one another as they juggle the changes coming their way"--